The appreciation of Malaysian Philosophy of Education among academics and how it relates to their productivity - Hassan, Aminuddin; Mat Rashid, Abdullah; Ismail, Ismi Arif; Ab Jalil, Habibah; Abd Rahman, Fadzilah (International Journal of Interdisciplinary Social Sciences, 2008)
This paper reveals the valuable perspectives of Malaysian academics in assessing the Malaysian Philosophy of Education (MPE) in terms of how successful its implementation is on Higher Education Institutions (HEI) in Malaysia. This research is also about productivity achievement. The researcher draws eight major conclusions in answering the main research questions. Firstly, the research argues that about 35%, 30% and 12% of the respondents have fair, good and very good knowledge about MPE respectively. All MPE elements are considered well implemented, where each of them has an average rating of more than 3 in an increasing scale of 1-5 (least to most). The most frequent constraint among the academics for MPE to be implemented in HEI is the significant burdens that are time consuming faced by them. Then, the most productive role among the academics is teaching, compared to research and administration. It is also argued that different factors give significant effect to different academic roles. An interesting figure of approximately 59% of the professors were thought to have been appointed on merit (deserve their appointment). There is a significant relationship between implementation success of MPE and administration productivity. Lastly, there is a significant relationship between the perspective of academics concerning professorial appointments and the successful implementation of MPE in HEI. However, the last two have modest correlation values in general. In conclusion, the study highlights the impacts of MPE in HEI alongside the possible constraints, and the outcomes of academics’ productivity by looking at their roles and the factors which affect their productivity. These two approaches could bring valuable positive indicators of the performance of current HEI in Malaysia as a whole.